Pathos as a communicative strategy for online knowledge dissemination:the case of TED talks - Giuseppina Scotto Di Carlo, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2015)
This paper investigates the importance of pathos in TED (Technology, Entertainment, Design) talks, which are popularising speeches aiming at Knowledge Dissemination. Drawing upon Dlugan's (2013) theories on the enhancement of pathos as a communicative strategy, this work analyses how pathos is established in this relatively new form of popularisation that breaches the typical ‘scientist-mediator-audiences’ triangularisation, bringing scientists directly into contact with their audiences. In particular, the study will focus on an exemplary TED talk held by Dr Jill Bolte Taylor, ‘My Stroke of Insight’, a fascinating TED talk that recounts the speaker’s first-person experience of a major stroke, and which has been one of the most watched TED talks so far, with over 12 million views. The study shows how pathos techniques are used by TED speakers to establish on-thespot connection with their live and online audiences by appealing to emotions and values. The work further suggests that the success of these talks depends on how these speakers are listened to, remembered, and perceived as credible promoters of knowledge dissemination, but also on how they contribute to audiences’ approach to science not as something distant and separate, but as a heritage belonging to both professionals and laypersons.